PENERAPAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) DI KUA KECAMATAN JATINANGOR KABUPATEN SUMEDANG - Juneldi, Rizel; Sururie, Ramdani Wahyu (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2020)
This research is motivated by the presence of an application in marriage data collection called the Marriage Management Information System or Simkah which has begun to be applied in various Religious Affairs Offices (KUA) in West Java, especially in KUA, Jatinangor District, Sumedang. Simkah is a policy program issued by the government to be applied to KUA in district which aims to facilitate the presentation of marriage data at the KUA. The purpose of this study was to describe the application of the Marriage Management Information System or Simkah in administrative services at KUA Jatinangor, Sumedang and its effectiveness. The method used in this research is descriptive method with a qualitative approach, namely research that seeks to reveal and interpret developing phenomena. In this case, the researcher went directly to the field, involving KUA Jatinangor, Sumedang Regency. The data found shows that Simkah at KUA Jatinangor, Sumedang Regency has been implemented but is still constrained, especially in terms of the readiness of the KUA's human resources. In some cases, it was found that it was difficult to use this application, including the complexity of inputting marriage data. Thus it can be concluded that the application of Simkah has helped facilitate data collection on marriages throughout Indonesia but it is still not effective in data entry at the local KUA.